Study of model distances on logical statements based on expert interpretation of the formulas of many-valued logics of Lukasiewicz and automatic clustering of knowledge bases. II - Vikent’ev А.А. (Bulletin of the Karaganda University. Mathematics Series, 2016)
In article the model range on logical statements based on expert interpretation of the formulas of many - valued logics of Lukasiewicz. The result of Theorem 2-4. Examples with the calculation of the distances between the formulas showing novelty metrics.